2007
DOI: 10.1016/j.metabol.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of subjects with type 2 diabetes mellitus may determine clinical response to chromium supplementation

Abstract: Background and Aims-Considerable controversy exists regarding use of chromium (Cr) supplementation to modulate carbohydrate metabolism in subjects with diabetes. Recently, we reported that Cr supplementation, provided as 1000 ug/day as Cr picolinate, enhanced insulin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 11 publications
3
40
1
2
Order By: Relevance
“…Baseline insulin sensitivity was found to account for nearly 40% of the variance in the clinical response to chromium. 25 In contrast, in this study, the baseline FPG levels in both the chromium and placebo groups were normal (Table 1). Our results are consistent with a meta-analysis finding no association between chromium and glucose or insulin concentrations among nondiabetic subjects.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Baseline insulin sensitivity was found to account for nearly 40% of the variance in the clinical response to chromium. 25 In contrast, in this study, the baseline FPG levels in both the chromium and placebo groups were normal (Table 1). Our results are consistent with a meta-analysis finding no association between chromium and glucose or insulin concentrations among nondiabetic subjects.…”
Section: Discussioncontrasting
confidence: 64%
“…24 Some reports suggest that chromium could suppress appetite and stimulate thermogenesis through sensitization of insulin-sensitive glucoreceptors in the brain. 25 Body fat distribution is related to insulin sensitivity; peripheral fat is more insulin sensitive than central fat found in the chest and abdomen. 26 A meta-analysis of 10 double-blind, placebo-controlled trials provides evidence of a relatively small reduction in body weight (1.1-1.2 kg over 10-13 weeks) in overweight and obese individuals receiving chromium picolinate.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the lack of effect of supplementation, CrPic can play an antioxidant effect when there is an oxidative disruption, because CrPic supplementation could preserve the antioxidant status when there are a depletion of antioxidant enzymes and an increase in oxidative stress [51][52][53]. In the present study, positive action of CrPic was not observed, likely because there was no depletion of antioxidant enzymes or increased oxidative stress in our sample.…”
Section: Discussionmentioning
confidence: 63%
“…Chromium is known for its beneficial influence on the glucose level in diabetic patients ( 20 , 21 ). The presumption is that chromium supplementation works whenever its blood level is low ( 21 ). However, chromium levels in diabetic patients are not examined before chromium supplementation.…”
Section: Discussionmentioning
confidence: 99%